Arabidopsis KETCH1 Is Critical for the Nuclear Accumulation of Ribosomal Proteins and Gametogenesis. Issue 4 (21st February 2020) - Xiong, Feng; Duan, Cun-Ying; Liu, Hai-Hong; Wu, Ju-Hua; Zhang, Zhong-Hui; Li, Sha; Zhang, Yan
Abstract : Arabidopsis KETCH1, an importin β, promotes the nuclear accumulation of ribosomal proteins and contributes to both male and female gametogenesis, likely by maintaining translational efficiency. Abstract: Male and female gametophytes are generated from micro- or megaspore mother cells through consecutive meiotic and mitotic cell divisions. Defects in these divisions often result in gametophytic lethality. Gametophytic lethality was also reported when genes encoding ribosome-related proteins were mutated. Although numerous ribosomal proteins (RPs) have been identified in plants based on homology with their yeast and metazoan counterparts, how RPs are regulated, e.g., through dynamic subcellular targeting, is unknown. We report here that an Arabidopsis ( Arabidopsis thaliana ) importin β, KETCH1 (karyopherin enabling the transport of the cytoplasmic HYL1), is critical for gametogenesis. Karyopherins are molecular chaperones mediating nucleocytoplasmic protein transport. However, the role of KETCH1 during gametogenesis is independent of HYPONASTIC LEAVES 1 (HYL1), a previously reported KETCH1 cargo. Instead, KETCH1 interacts with several RPs and is critical for the nuclear accumulation of RPL27a, whose mutations caused similar gametophytic defects. We further showed that knocking down KETCH1 caused reduced ribosome biogenesis and translational capacity, which may trigger the arrest of mitotic cell cycle progression and lead to gametophytic lethality.